The central government of Russia : from Gorbachev to Putin / Iulia Shevchenko. - Shevchenko, Iulia. (Post-Soviet politics., 2004)
"Placing the development of the Soviet and Russian central governments in theoretical context, this work breaks new ground in the study of contemporary Russian politics. Iulia Shevchenko's treatment of the principal-agent model offers fresh insight into the institutional origins of change in government organization in the communist and post-communist period, from President Gorbachev to President Putin. She demonstrates that government organization varies with the extent to which the principal actors - the president and parliament - are prepared to empower the cabinet to actively develop rather than just implement policy.